Impact of an intense water column mixing (0–1500 m) on prokaryotic diversity and activities during an open‐ocean convection event in the NW Mediterranean Sea. (2nd June 2016) - Severin, Tatiana; Sauret, Caroline; Boutrif, Mehdi; Duhaut, Thomas; Kessouri, Fayçal; Oriol, Louise; Caparros, Jocelyne; Pujo‐Pay, Mireille; Durrieu de Madron, Xavier; Garel, Marc; Tamburini, Christian; Conan, Pascal; et al.
Summary: Open‐ocean convection is a fundamental process for thermohaline circulation and biogeochemical cycles that causes spectacular mixing of the water column. Here, we tested how much the depth‐stratified prokaryotic communities were influenced by such an event, and also by the following re‐stratification. The deep convection event (0–1500 m) that occurred in winter 2010–2011 in the NW Mediterranean Sea resulted in a homogenization of the prokaryotic communities over the entire convective cell, resulting in the predominance of typical surface Bacteria, such as Oceanospirillale and Flavobacteriales . Statistical analysis together with numerical simulation of vertical homogenization evidenced that physical turbulence only was not enough to explain the new distribution of the communities, but acted in synergy with other parameters such as exported particulate and dissolved organic matters. The convection also stimulated prokaryotic abundance (+21%) and heterotrophic production (+43%) over the 0–1500 m convective cell, and resulted in a decline of cell‐specific extracellular enzymatic activities (−67%), thus suggesting an intensification of the labile organic matter turnover during the event. The rapid re‐stratification of the prokaryotic diversity and activities in the intermediate layer 5 days after the intense mixing indicated a marked resilience of the communities, apart from the residual deep mixed water patch.